Increased B-type Natriuretic Peptide (NT-proBNP) Level as a Risk Factor in Cardiosurgical Patients - I. A. Kozlov; I. Ye. Kharlamova (Общая реаниматология)
Objective: to study the impact of increased inactive (N-terminal) pro-B-type natriuretic peptide (NT-proBNP) levels in cardiosurgical patients with coronary heart disease without drastically reducing left ventricular contractility on intraoperative central hemodynamics and the specific features of therapeutic measures for its stabilization. Subjects and methods. The inclusion criteria were elective surgery, age less than 70 years, a left ventricular ejection fraction of at least 30%, and no surgical complications. Sixty-one patients aged 54.6±1.2 years with a left ventricular ejection fraction of 51. 5 ± 1. 6 %. Before surgery, NT-proBNP was determined by electrochemiluminiscence («Elescys®proBNP»). Invasive hemodynamic monitoring was made with Swan-Ganz catheters. Results. The level of NT-proBNP was 13.2—3232 pg/ml. When the preperfusion values of the biomarker was more than 350 pg/ml, the magnitude of a peptide concentration increase affected that of an elevation of pulmonary artery wedge pressure (r=0.52; p=0.002) and that of a decrease in left ventricular pump coefficient (r=-0.44; p=0.01). At the end of operations, this patient group, as compared with the others, had a lower left ventricular pump coefficient (2.9±0.2 and 3.9±0.3 g/mm Hg/m2; p<0.05) and the dosages of dopamine and/or dobutamine were increased (4.3±0.3 and 3.1±0.3 ^g/kg/min; p<0.05). The degree of NT-proBNP elevations correlated with stroke volume index (r=-0.42; p=0.02), the dosages of dopamine and/or dobutamine (r=0.38; p=0.04) and epinephrine and/or norepinephrine (r=0.66; p<0.001). NT-proBNP levels of 1100 pg/ml or more was a significant predictor (p<0.0001) of extracorporeal circulation. When the level of NT-proBNP was less than 350 pg/ml, the clinical course of operations was satisfactory in 96.6%. Biomarker variations in the range of up to 350 pg/ml failed to affect cardiac pump function before and after extracorporeal circulation and the dosages of inotropic agents at the end of operations. Conclusion. The increased NT-proBNP level that characterizes B-type natriuretic peptide hypersecretion is a risk factor for cardiac dysfunction after myocardial revascularization under extracorporeal circulation. This value of the biomarker is 350 pg/ml for patients aged under 70 years with a left ventricular ejection fraction of at least 30%, the level of 1100 pg/ml or higher being a predictor of heart failure that requires assisted circulation.